Comparative Study on Reagents Involved in Grape Bud Break and Their Effects on Different Metabolites and Related Gene Expression during Winter - Khalil-Ur-Rehman, Muhammad; Wang, Wu; Xu, Yan-Shuai; Haider, Muhammad S.; Li, Chun-Xia; Tao, Jian-Min (Frontiers in Plant Science, 2017)
To elucidate promoting and inhibiting effects of hydrogen cynamide (HC) and abscisic acid (ABA) on quiescence release of grape buds, physiological and molecular approaches were used to explore the mechanisms of quiescence based on metabolic and gene expression analysis. Physiological and molecular mechanisms involved in bud quiescence of grape were studied before and after application of HC, ABA and ABA-HC. The data showed that ABA inhibited quiescence release in grape buds and attenuated the effect of HC. Bud quiescence was promoted and regulated by HC and ABA pre-treatment on buds of grape cultivar “Shine Muscat” with 5% HC ,100 μM ABA and combination of ABA-HC(5% HC+100 μM ABA) during quiescence under forcing condition. Exogenous application of ABA enhanced the activities of ascorbate peroxidase (APX), peroxidase (POD) and superoxide dismutase (SOD) while activity of catalase (CAT) increased during initial period of forcing and then decreased. The concentration of plant growth hormones including gibberellins (GA) and indole acetic acid (IAA) increased by HC application but decreased the ABA contents under forcing condition. ABA increased the fructose content during quiescence under forcing condition while sucrose and total soluble sugars peaked in HC treated buds as compared to control. Genes related to ABA pathway, protein phosphatase 2C (PP2C family) were down regulated in the buds treated with HC, ABA and ABA-HC as compared to control while two genes related to GA pathway (GID1 family), out of which one gene showed down regulation during initial period of forcing while other gene was up regulated in response to HC and ABA-HC treatments as compared to control. Exogenous ABA application up regulated genes related to antioxidant enzymes as compared to control. The gene probable fructose-bisphosphate aldolase 1, chloroplastic-like, was up regulated in response to ABA treatment as compared to control. Analysis of metabolites and related gene expression pattern would provide a comprehensive view of quiescence after HC, ABA and ABA-HC treatments in grape buds which may helpful for ultimate improvement in table grape production.